The Ocean Carbon Response to COVID‐Related Emissions Reductions. Issue 6 (25th March 2021) - Lovenduski, Nicole S.; Swart, Neil C.; Sutton, Adrienne J.; Fyfe, John C.; McKinley, Galen A.; Sabine, Christopher; Williams, Nancy L.
Abstract: The decline in global emissions of carbon dioxide due to the COVID‐19 pandemic provides a unique opportunity to investigate the sensitivity of the global carbon cycle and climate system to emissions reductions. Recent efforts to study the response to these emissions declines has not addressed their impact on the ocean, yet ocean carbon absorption is particularly susceptible to changing atmospheric carbon concentrations. Here, we use ensembles of simulations conducted with an Earth system model to explore the potential detection of COVID‐related emissions reductions in the partial pressure difference in carbon dioxide between the surface ocean and overlying atmosphere (ΔpCO2 ), a quantity that is regularly measured. We find a unique fingerprint in global‐scale ΔpCO2 that is attributable to COVID, though the fingerprint is difficult to detect in individual model realizations unless we force the model with a scenario that has four times the observed emissions reduction. Plain Language Summary: The COVID‐19 pandemic is slowing the rate of fossil fuel use, and thus impacting the carbon dioxide concentration in the atmosphere. Here we explore what this change in fossil fuel use does to carbon in the ocean. We use a climate model to estimate the change in ocean‐atmosphere carbon exchange and ocean acidity. Since we don't yet know how much we will slow our fossil fuel use due to COVID, we make several informed guesses and see how our model ocean responds to each. We use the model to investigate whether the change that we model would be detectable in real world observations. We find that it is nearly impossible to detect a COVID‐related change in ocean acidity with observations. It might be possible to detect a COVID‐related change in ocean‐atmosphere carbon exchange, but only if we use the most extreme guess, and only if we have enough observation stations in place to record it. Key Points: COVID‐related emissions reductions will be imperceptible in surface ocean pH observations The CanESM5 COVID ensemble predicts a unique fingerprint of COVID‐related emissions reductions in global mean ΔpCO2 (p C O 2 o c ‐ p C O 2 a t m ) The fingerprint is potentially detectable in global‐scale observations of ΔpCO2, but only with large emissions reductions